THE CONCEPT OF PUBLIC CONTROL IN THE VIEWS OF EASTERN AND WESTERN SCIENTISTS AND ITS SOCIO-PHILOSOPHICAL SIGNIFICANCE IN MODERN PRACTICE (TAMADDUN NURI JURNALI, 2024)
This article analyzes the content of the phenomenon of public control, which is the primary basis for building a civil society in the history of mankind in the views of Eastern and Western thinkers of antiquity, the Middle Ages and Modern Times, the concept of public control, mechanisms of public control and its significance in practice, legal norms for ensuring public control in our country.